Mi lett fontos a pandémia alatt? Preferenciák, vásárlói szokások átértékelődése a koronavírus-járvány hatására a különböző generációk szemével - Csiszárik-Kocsir, Ágnes; Garai-Fodor, Mónika; Varga, János (Vezetéstudomány / Budapest Management Review, 2022)
Since the pandemic, consumer preferences and the contents of consumers’ baskets have changed. Each generation has different views on the impact of the virus on different areas of our lives, which is largely related to the general set of values that characterizes each generation. The focus of this research is the relationship between the generation-specific value system and the changes in consumer behaviour caused by the virus. In the primary data analysis, the authors examined two hypotheses regarding how (H1) consumer habits were modified by the pandemic; what they purchased; (H2) the differing customer habits of each generation (H2 /a) and how these are related to the individual’s value system (H2 /b). In the light of the results, the authors were able to determine how the composition of the content of the consumer basket changed by analyzing specific generational contexts in connection with which product and service purchase came to the fore as a result of the crisis.